Hubungan Tingkat Pendidikan dan Dukungan Keluarga dalam Pemberian Asi Eksklusif pada Bayi Usia 0-6 Bulan di Puskesmas Talang Bakung Kota Jambi - Anggraini, Sari; Rahmah, Rahmah; Haryati, Dwi; Monica, Olivia Tri (Universitas Malahayati, 2023)
ABSTRACT WHO shows that the Infant Mortality Rate in Indonesia is still at 21.86/10000 live birth, with a target of 2025 the coverage of exclusive breastfeeding in the first 6 months of birth increases by 50%. In Jambi Province, the coverage of exclusive breast feedin in 2020 reached 59.9 which has not met the national achievement target. The role of education level and family support greatly influences mothers in exclusive breastfeeding. This study aims to determine the relationship between education level and family support in exclusive breastfeeding at the Talang Bakung Health Center, Jambi City. The research method uses decrictive analytic with a cross sectional approach, with the population being mothers who have babies aged 0-6 months who visit the Talang Bakung Health Center, Jambi City. The sample selection used a purposive sampling technique, with a total sample of 38 mothers who had babies aged 0-6 months. The instrument used is a questionnaire. Bivariate analysis using chi-square test. Most of the respondents were included in the category of higher education as many as 29 respondents (76.3%), and most of the respondents were included in the category of having positive family support as many as 27 respondents (71.1%). Statistical test results showed a significant relationship between education level (p-value 0.049) and family support (p-value 0.001) with exclusive breastfeeding at the Talang Bakung Health Center, Jambi City. There is a signifant relationship between education level and family support with exclusive breastfeeding at the Talang Bakung Health Center, Jambi City. Education about exclusive breastfeeding can be used as a community service program carried out by local health centers in work areas to increase the coverage of exclusive breastfeeding. Keywords: Education Level, Family Support, Exclusive Breastfeeding. ABSTRAK WHO menunjukkan Angka Kematian Bayi di Indonesia masih diangka 21,86/1000 kelahiran hidup, dengan target tahun 2025 cakupan pemberian ASI eksklusif pada 6 bulan pertama kelahiran meningkat 50%. Di Provinsi Jambi, cakupan ASI eksklusif tahun 2020 mencapai 59,9%, dimana jumlah tersebut belum memenuhi target capaian nasional. Peran tingkat pendidikan dan dukungan keluarga sangat mempengaruhi ibu dalam pemberian ASI ekskslusif. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pendidikan dan dukungan keluarga dalam pemberian ASI ekskslusif di Puskesmas Talang Bakung Kota Jambi. Metode penelitian menggunakan deskriptif analitik dengan pendekatan cross sectional, dengan populasi adalah ibu yang memiliki bayi usia 0-6 bulan yang berkunjung ke Puskesmas Talang Bakung Kota Jambi. Pemilihan sampel menggunakan teknik purposive sampling, dengan jumlah sampel sebanyak 38 orang ibu yang mempunyai bayi usia 0-6 bulan. Instrumen yang digunakan adalah kuesioner. Analisa bivariat menggunakan uji chi-square. Sebagian besar responden termasuk dalam kategori pendidikan tinggi sebanyak 29 responden (76,3%), dan sebagian besar responden termasuk dalam kategori mendapat dukungan keluarga secara positif sebanyak 27 responden (71,1%). Hasil uji statistik menunjukkan terdapat hubungan yang signifikan tingkat pendidikan (p-value 0,049) dan dukungan keluarga (p-value 0,001) dengan pemberian ASI eksklusif di Puskesmas Talang Bakung Kota Jambi. Terdapat hubungan yang signifikan tingkat pendidikan dan dukungan keluarga dengan pemberian ASI eksklusif di Puskesmas Talang Bakung Kota Jambi. Edukasi tentang pemberian ASI eksklusif dapat dijadikan program pengabdian masyarakat yang dilakukan oleh puskemas setempat di wilayah kerja untuk peningkatan cakupan ASI eksklusif. Kata Kunci: Tingkat Pendidikan, Dukungan Keluarga, Pemberian ASI Eksklusif